Clinical significance of interleukin-6 measurement in early rheumatoid arthritis: relation with laboratory and clinical variables and radiological progression in a three year prospective study. - van Leeuwen, M A (1995)
OBJECTIVE--To evaluate the clinical significance of interleukin-6 (IL-6) measurements in relation to laboratory and clinical measures of disease activity and radiological progression in early rheumatoid arthritis (RA). METHODS--A prospective study was performed in 51 patients with early RA during the first three years of the disease, with monthly clinical and laboratory assessments and biannual radiographs of the hands and feet. IL-6 was measured by enzyme linked immunosorbent assay (ELISA). Cross sectional (n = 51) and longitudinal (n = 20) correlations between plasma IL-6 concentrations and values of C reactive protein (CRP), serum amyloid A protein (SAA), erythrocyte sedimentation rate (ESR), haemoglobin (Hb), platelets, and joint scores were calculated, and correlations made between time integrated values of IL-6, CRP and ESR, and radiological progression over three years (n = 20). RESULTS--Significant correlations were found between IL-6 and the acute phase response and platelets, but variable results were obtained for the correlation between IL-6 and Hb. In contrast to a significant correlation between time integrated values of CRP or ESR and radiological progression, time integrated values of IL-6 did not correlate with radiological progression over three years follow up. CONCLUSION--The course of disease activity and the radiological progression of joint damage are better reflected by CRP, SAA, and ESR values than by plasma IL-6 concentrations, particularly in stages of low disease activity.